Pengembangan Sistem Informasi Akademik Universitas Serang Raya (Infosera) Berbasis Mobile Android - Ibrohim, Muhamad; Hermawan, Arwan (Universitas Serang Raya, 2016)
Android Technology developments are currently Singer Many developers use App Good for Personal Needs and Institutional review. SERVICES AT information Already Running University Raya Serang When Singer Must Can follow the development of Android technology. By THEREFORE, built-Based Information Systems Applications Android WITH academic purposes as a Options (complementary) System that can be meet the ADA Requirements The information can be accessed through a mobile device to review AKSes facilitate Yang MORE FLEXIBLE. Mobile phone applications are built Implement Three Technologies That Service Background Android and Push Notification The function to run an application in the Rear Screen for review checking ON database server And MAKE Notification Under Condition What is desired, JSON Its function is to review data exchange BETWEEN Android smartphone web server WITH, web and services Yang serves as the program provider information data. From the findings of Information System Implementation academic AT THE University of Serang Kingdom Singer, can be concluded that Information Systems Academic singer can be Running Platform AT Android And has Able to function WITH Good Namely Charging Study Plan Card (KRS), information Study Result Card (KHS) Library and information books.